Welcoming people living with HIV in a specialized care service: an experience report from the perspective of a resident nutritionist (Research, Society and Development, 2022)
The reception of people living with HIV (PLHIV) translates into a powerful tool in the health-disease process because it helps the user clarify their doubts about the disease and recognize risk situations and vulnerabilities, expose fears and concerns, and create a bond with the professional, staff and health service. Thus, the study aims to report the experience of a nutrition resident working in a specialized care service allocated in a university hospital in Alagoas, facing the reception of PLHIV. This is a descriptive study, of the experience report type, derived from the activities and care actions developed during the multidisciplinary residency program in health, in the adult and elderly area, in the biennium 2020-2022. The report was structured in four guiding axes of discussion, with the approach of different relevant themes for the performance of the professional nutritionist, formulated from the concerns that emerged during training in a multidisciplinary residency program in health. Inadequate reception can be translated into the distance between the individual and the health service, which reverberates in individual and/or collective consequences. During the formation of the nutritionist, discussions based on a single and exclusively biological being, in addition to the focus on dietary prescription, may limit the vision and performance of the professional in training, thus, it is necessary that the training process is revisited and that the biomedical model of care is reassessed.